Factors associated with switching from sulphonylureas to dipeptidyl peptidase 4 inhibitors among patients with type 2 diabetes in the United States. Issue 10 (6th July 2021) - Tan, Xi; Yang, Lingfeng; Khunti, Kamlesh; Zhang, Ruya; Zhang, Ye; Rajpathak, Swapnil; Yu, Miao
Abstract: Aims: Studies examining the prevalence of and factors associated with switching from sulphonylureas (SUs) to dipeptidyl peptidase 4 (DPP‐4) inhibitors in real‐world settings are lacking. We assessed the factors associated with switching from SUs to DPP‐4 inhibitors in the United States. Materials and Methods: This retrospective cohort study was conducted using the Optum Clinformatics® Data Mart (2009‐2018). Adults with type 2 diabetes and newly prescribed at least two SUs were included and were followed for 2 years after the initiation of SU (index date). We compared the characteristics of those who switched from SUs to DPP‐4 inhibitors (only; no additional antidiabetic drugs) with those who continued with SUs (without adding other antidiabetic drugs) using multivariate logistic regression. Multinomial regression analyses were also conducted to assess the factors associated with switching to different drug classes versus continuation with SUs. Results: In a sample of 119 107 new SU users, 2.2% (2633) switched to DPP‐4 inhibitors, 3.8% (4542) switched to antidiabetic drugs other than DPP‐4 inhibitors, 68.3% (81 394) discontinued SUs but did not switch to another antidiabetic drug, 12.9% (15 345) continued with SUs and added other antidiabetic drugs, and 12.8% (15 193) continued with SUs only. Multivariate logistic regression showed that those who had significantly higher likelihood of switching were younger, female [vs. males; adjusted odds ratio (AOR) = 0.70], and living in the south; had previous use of DPP‐4 inhibitors (AOR = 1.71); were not using antidiabetic drugs at baseline; had more baseline diabetes‐related emergency room visits (AOR = 1.13), depression (AOR = 1.34), post‐index hypoglycaemia (AOR = 2.20), and an earlier index year; and were glyburide users (vs. glimepiride users; AOR = 1.29). Conclusions: The discontinuation rate for SUs is high. Factors associated with switching from SUs to DPP‐4 inhibitors included age, sex, geographic region, baseline antidiabetic drug use, type of SU, baseline diabetes‐related emergency room visits, hypoglycaemia and depression.